Development and Adaptation of an Employment-Integration Program for People who are Visually Impaired in Quebec, Canada. (November 2013) - Wittich, Walter; Watanabe, Donald H.; Scully, Lizabeth; Bergevin, Martin
Introduction: In the Province of Quebec, Canada, it is estimated that only about one-third of working-age adults with visual impairments are part of the workforce, despite ongoing efforts of rehabilitation and government agencies to integrate these individuals. The present article describes the development and adaptation of a pre-employment program specifically designed for English-speaking visually impaired persons in Quebec. Methods: Based on a model program introduced at the University of Texas in the United States, and further developed with the Royal National Institute of Blind People in the United Kingdom, the MAB-Mackay Rehabilitation Centre (MMRC) adapted the training materials for its pre-employment program to the local requirements. Its effectiveness was appraised using posttraining employment status as well as responses by participants, using the Canadian National Institute for the Blind (CNIB) Tool to Assess Preparedness for Employment (TAPE) measure of employment readiness. Results: Of the eight participants who completed the four-week program, five had found employment and, of those, four had maintained employment within the eight-month follow-up period (one full-time, three part-time). Further, two of those employed part-time also returned to school part-time. An additional two participants chose to continue their education in order to improve their employability. Scores on the CNIB TAPE subscale of communication showed statistically significant post-training improvement (p = .01) that was maintained after eight months. A statistical trend indicated improvement on the technology subscale following participation in training (p = .10). Discussion: MMRC's pre-employment training program was developed to address the need for a structured employment preparation program that was integrated with the available rehabilitation services for English-speaking visually impaired individuals in a predominantly French-speaking environment. Implications for practitioners: The multidisciplinary nature of this approach facilitated a common language and shared perspective for practitioners across disciplines that are involved in preparing clients for the job market.